2010
DOI: 10.1007/bf03213738
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy and uninsured: Exploring racial differences in health and health insurance coverage using a life table approach

Abstract: Millions of people in the United 2002a;Osteen et al. 1994;Roetzheim et al. 1999). Being uninsured also poses serious fi nancial threats to Americans, with millions carrying a large burden of debt from medical expenses ( Himmelstein et al. 2005). Although public programs-such as Medicaid and the State Children's Health Insurance Program (SCHIP)-provide health insurance to many who would otherwise not be able to afford coverage, millions are without health insurance.In this article, we argue that current researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 38 publications
(41 reference statements)
0
76
1
3
Order By: Relevance
“…This finding is important in light of recent research suggesting an insurance gap for the near elderly, in general, and preretirement women whose spouses have retired, in particular Kirby & Kaneda, 2010). It may be religious participation facilitates awareness of or access to alternative means of health insurance.…”
Section: Discussionmentioning
confidence: 73%
“…This finding is important in light of recent research suggesting an insurance gap for the near elderly, in general, and preretirement women whose spouses have retired, in particular Kirby & Kaneda, 2010). It may be religious participation facilitates awareness of or access to alternative means of health insurance.…”
Section: Discussionmentioning
confidence: 73%
“…Unfortunately in the United States, access to healthcare significantly differs by race [13], which may largely account for observed cancer-related outcomes due to treatment barriers. Besides possible differences in tumor biology, this could account for the apparent worse survival in black patients with RCC.…”
Section: Original Researchmentioning
confidence: 99%
“…Multiple studies at the individual, community and census-tract levels suggest that minority women of lower SES have much lower screening rates, after extensive adjustments for cofounders [68]. One multilevel study of black women found that those living in census tracts with <5% poverty, compared to women living in high-poverty areas (defined by >20% poverty), were 1.2-fold less likely to have undergone cervical cytology screening within the last 2 years [65,69]. …”
Section: Incomementioning
confidence: 99%